Review articleTreatment of systemic vasculitis – clinical aspects - Swarowska-Knap, Justyna; Tłustochowicz, Witold (Reumatologia/Rheumatology, 2007)
Systemic vasculitis is treatable but not curable. Combination therapy with corticosteroids and immunosuppressives induces remission in approximately 90% of cases. Treatment employing cyclophosphamide and prednisone has improved prognosis, but relapses and treatment-induced side effects still cause severe morbidity and frequent mortality. The optimal doses and duration of the treatment remain to be clarified in the large multicentre randomized trials. Patients with vasculitis should be treated as soon as possible. Treatment should not be delayed until a definitive diagnosis is made. For patients with mild forms of vasculitis, initial therapy with corticosteroids and agents other than cyclophosphamide may be adequate to induce remission. Patients with poor prognostic factors (FFS>0) require therapy with corticosteroids and cyclophosphamide. Usually disease has remitted or markedly improved after 3-6 months and later transition to alternative agents is possible for most patients.